Blood and salivary lactate responses to active rest following circuit exercise - Kojima, Chihiro; Morishima, Takuma; Ito, Reita; Yasunaga, Sosuke; Shimogaki, Takumi; Hashimoto, Takeshi; Isaka, Tadao; Iemitsu, Motoyuki (Frontiers in Physiology, 2025)
The present study investigated blood and salivary lactate concentrations with or without active recovery following intensive exercise. Seven men and four women were randomly assigned to two trials consisting of a control (CON) trial and an active recovery (AR) trial separated by at least 1 week. In both trials, participants performed total 30 min of circuit exercise for lower extremities. Afterwards, in the AR trial, participants completed 15 min of light cycling exercise; in the CON trial, participants remained seated during postexercise. Blood and salivary concentrations were measured before and immediately after the circuit exercise, immediately after each trial, and the next morning, using a portable device. Blood lactate concentrations increased significantly immediately after circuit exercise in both trials (AR: 11.9 ± 2.9 mmol/L, CON: 13.4 ± 3.0 mmol/L, P < 0.05), and a significant difference was observed between trials, immediately after each trial (AR: 4.2 ± 1.4 mmol/L, CON: 6.9 ± 2.8 mmol/L, P < 0.05). In addition, both trials showed salivary lactate concentrations increased significantly following circuit exercise (AR trial: 4.4 ± 3.0 mmol/L, CON trial: 5.4 ± 3.9 mmol/L, P < 0.05), and there was a significant difference between trials after the intervention (AR trial: 0.8 ± 0.4 mmol/L, CON trial: 3.1 ± 2.0 mmol/L, P = 0.007). In addition, there was a significant correlation between blood and salivary lactate concentrations during the postexercise period (r = 0.856, P < 0.001). Thus, salivary lactate concentrations may reflect relative changes in blood lactate concentrations during the postexercise period with active recovery following intensive exercise.